Módulo elástico como ferramenta para o acompanhamento de transformações in situ e desenvolvimento de concretos refratários - Souza, Tiago Marcolino de (2012)
Refractory castables are multiphase materials usually exhibiting complex heterogeneous microstructures, which have their mechanical strength affected by chemical and structural changes. These microstructural changes directly affect the Young s modulus, as this property is strongly dependent on the chemical bonds, crystalline structure and flaws, such as porosity and cracks. For the Al2O3-MgO system, two transformations can be highlighted: the volumetric expansion associated with the magnesia hydration and the in situ spinel formation, both can play a role by increasing or decreasing the castable s embrittlement depending on the resulting expansion. Considering this aspect, the addition of MgO sources with different reactivity in refractory castables was evaluated during curing and drying steps. As a result, different routes for magnesia s sources addition to the castables, without the usual damage caused by MgO hydration, are presented in this work. The addition of acetic acid sped up the brucite precipitation, inducing the formation of a resilient structure able to inhibit the stresses generation. Additionally, the effect of mineralizing or densification compounds on spinel-forming castables and the microstructural evolution of refractory castables containing different MgO sources, colloidal binders or high-carbon content were assessed during the thermal treatment by hot Young s modulus measurements using the resonance bar technique. The attained results highlight the technique s broad feature and accuracy for the development of refractory materials. The MgF2 and magnesium borate addition sped up the spinel formation, whereas TiO2 led to lower expansion values and greater rigidity at high temperatures, all of them as promising alternatives to master the castable s microstructure design. For the nano-bonded castables, the sintering additive addition further enhanced the Young s modulus resulting in high-performance refractories. Additionally, the elastic modulus measurements were able to evaluate the antioxidants effect in high-carbon containing castables and to identify the mechanisms of crack healing (during heating) and opening (during cooling).